Peran Ulama Dalam Perkembangan Institusi Pendidikan Islam Mathlaul Anwar Dan MALNU - Bahri, Saepul (Universitas Cokroaminoto Yogyakarta, 2023)
The teachings of Islam, with the role of scholars, have become dynamic, renewable, and robust in facing the challenges of the times. Scholars are capable of solving problems and providing solutions for religious activities that arise in the digital era. The research method used, namely the